The interaction of social influence and message framing on children’s food choice - Khan, Huda; Lee, Richard; Khan, Zaheer (Emerald, 2022)
Purpose Obesity leads to increased mortality and morbidity among children, as well as when they turn adults. Melding marketing theories in social influence and message framing, this study aims to examine how compliance versus conformance social influence, each framed either prescriptively or proscriptively, may guide children’s choice of healthy versus unhealthy food. Design/methodology/approach This study conducted two experiments in a Pakistani junior school. Experiment 1 exposed children to either a prescriptive or a proscriptive compliance influence. Experiment 2 involved a 2 (prescriptive vs proscriptive compliance influence) × 2 (supportive vs conflicting conformance-influence) between-subjects design. Participants in both studies answered an online survey after being exposed to the social-influence messages. Findings Experiment 1 showed proscriptive was stronger than prescriptive compliance influence in nudging children to pick fruits (healthy) over candies (unhealthy). However, frequency of fruits dropped as susceptibility to compliance strengthened. Experiment 2 found that a proscriptive compliance influence reinforced by a supportive conformance-influence led to most children picking fruits. However, a conflicting conformance influence was able to sway some children away from fruits to candies. This signalled the importance of harmful peer influence, particularly with children who were more likely to conform. Research limitations/implications Childhood is a critical stage for inculcating good eating habits. Besides formal education about food and health, social influence within classrooms can be effective in shaping children’s food choice. While compliance and conformance influence can co-exist, one influence can reinforce or negate the other depending on message framing. Practical implications In developing countries like Pakistan, institutional support to tackle childhood obesity may be weak. Teachers can take on official, yet informal, responsibility to encourage healthy eating. Governments can incentivise schools to organise informal activities to develop children’s understanding of healthy consumption. Schools should prevent children from bringing unhealthy food to school, so that harmful peer behaviours are not observable, and even impose high tax on unhealthy products or subsidise healthy products sold in schools. Originality/value This study adopts a marketing lens and draws on social influence and message framing theory to shed light on children’s food choice behaviour within a classroom environment. The context was an underexplored developing country, Pakistan, where childhood obesity is a public health concern.
Keywords: child obesity; compliance influence; conformance influence; prescriptive message; proscriptive message